Delivering a sports participation legacy from the London 2012 Olympic and Paralympic Games: evidence from sport development workers in Birmingham and their experiences of a double-bind. Issue 5 (2nd September 2020) - Lovett, Emily; Bloyce, Daniel; Smith, Andy
ABSTRACT: Legacy promises from London 2012 meant that those working in sport in local, non-host areas in Britain were expected to facilitate more sporting opportunities for local citizens. Legacy preparations occurred in the context of many other constraints that stemmed from Government budget cuts and provision of leisure-time sport and other leisure activities. This paper presents new evidence on a significantly under-researched area of leisure studies, namely: the experiences of those delivering leisure-sport opportunities in a non-host city and how they responded to national legacy promises. Using Elias's concept of the double-bind, we explain the 'crisis situation' in which some local sports workers were enmeshed and how their acceptance of 'fantasy-laden beliefs' of expected demonstration effects from mega-events exacerbated their 'crisis'. We also draw upon participants' post-Games reflections to consider how future host nations may wish to leverage greater leisure-sporting legacies from a mega-event.